Análisis de audiencia en la red social facebook del medio digital click de la ciudad de Babahoyo, en el primer trimrestre 2019 - Vera García, Graciela Roxana (2019)
The aggregation of social networks, has given rise to a new notion of the audience activated social audience, the interaction of audiences with the media has been excavated with the new medical habit, has been disclosed, conceiving audiences. A data system that allows them to improve the quality of information. Sociability intervene with your contacts and acquirers in this way a now mutual experience, social networks must be seen as a tool that helps in the training processes, audience measurement now faces challenges that start from systematized innovation. The digital audience is becoming more complex every day, currently the migration of audiences to digital media makes online platforms increasingly important. The media didactic communication, there is dialogue with the observable audience. The social networks, originated a growth in the increase of favorable information, assuming as a consequence that people are perseverantly encompassed by data and news content. When talking about virtual diversity, we refer to people with a common interest who are looking for an end that also enriches and favors organizations due to the current complexity of the agreement to Facebook statistics, approximately 82% of the beneficiaries among the most used Frequent Facebook are personal social networks, pages of public and private entities. Google and Facebook show the decision to participate as distribution platforms in support of submerged multimedia formats, the momentum of the virtual situation has had a daring to join this process. The journalist today has to be ready for the technological world, it is competitive that he executed multitasking, knows the incomparable supports on the internet